El Excentrico, 1961-12-05 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
December 5, 1961 [5 de diciembre de 1961] Ano 12, No 4. Cover has a photograph of Ted Cervantez receiving a Club Champion award from Lillian Lozano, who achieved the title of Miss Los Amigos Golfing Club of 1961.